Antioxidant and Anticancer Activities of Spatholobus littoralis Stem Extract: An In Vitro and In Silico Computational Investigation - Rustandi, Tedi; Yumassik, Abdul Mahmud; Nugraha, Elza Julian Eka Putri; Nugroho, Muhammad Riko; Yasir, Muhammad; Kamalia (Journal of Food and Pharmaceutical Sciences, 2025)
The stem of Spatholobus littoralis has been used to treat cancer and is empirically utilized by the Dayak people on the island of Kalimantan, Indonesia. This study aims to explore the antioxidant activity of Bajakah stems extracted using nine different solvent variations and to test their anticancer activity and toxicity in silico. The in vitro methods used to assess antioxidant activity are the DPPH and ABTS assays. The applications utilized for the in silico methods include SwissADME, Deep-PK, ProTox 3.0, STITCH, and AutoDock Vina. The test results show that the antioxidant activity of the 70% ethanol extract has a good profile. Meanwhile, the toxicity test of the contained bioactive compounds indicates a good safety level with a minimum IC50 value of 1034 mg/kg. The bioactive compounds exhibit good affinity, with the highest values for the bioactive daidzein at receptors 1di8 and 3twj, with values of -9.5 and -8.8, respectively. It can be concluded from this study that the stem of Spatholobus littoralis has potential as an anticancer agent, although its antioxidant potential is low.